2009
DOI: 10.1016/j.econlet.2009.04.012
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation of endowment source heterogeneity in two-person public good games

Abstract: We find an "inverse found money effect" in two-person public good experiments in which individuals earning their endowments contribute more and engage in "altruistic conditional cooperation" when they are matched with those whose endowment is provided by the experimenters.Published by Elsevier B.V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…Although emotions, social value orientation, and other individual differences are important for understanding the antecedents of fair bargaining (e.g., Stephen & Pham, 2008;van Dijk et al, 2004), there is some evidence that fairness is contextspecific or relationship-specific, varying with the information presented or the domain of the social interaction (e.g., Fiddick & Cummins, 2007). A few recent studies have even altered the context of bargaining games (e.g., dictator, public goods) to reveal that transactions are affected if proposers and responders are given property rights to the pot of money (Cherry, Frykblom, & Shogren, 2002;Leliveld, van Dijk, & van Beest, 2008;List, 2007;Oxoby & Spraggon, 2008;Spraggon & Oxoby, 2009;van Dijk et al, 2004). Additionally, changing the bargaining situation evokes different social norms which in turn influence fairness perceptions (Gamliel & Peer, 2006;Konow, 2003;Leliveld et al, 2008;March, 1994;Messick, 1999).…”
mentioning
confidence: 99%
“…Although emotions, social value orientation, and other individual differences are important for understanding the antecedents of fair bargaining (e.g., Stephen & Pham, 2008;van Dijk et al, 2004), there is some evidence that fairness is contextspecific or relationship-specific, varying with the information presented or the domain of the social interaction (e.g., Fiddick & Cummins, 2007). A few recent studies have even altered the context of bargaining games (e.g., dictator, public goods) to reveal that transactions are affected if proposers and responders are given property rights to the pot of money (Cherry, Frykblom, & Shogren, 2002;Leliveld, van Dijk, & van Beest, 2008;List, 2007;Oxoby & Spraggon, 2008;Spraggon & Oxoby, 2009;van Dijk et al, 2004). Additionally, changing the bargaining situation evokes different social norms which in turn influence fairness perceptions (Gamliel & Peer, 2006;Konow, 2003;Leliveld et al, 2008;March, 1994;Messick, 1999).…”
mentioning
confidence: 99%
“…Experimental results from a prisoner's dilemma experiment with heterogeneous initial endowments but homogeneous benefits suggest that subjects earning their endowments contribute more to the joint project when they are matched with subjects whose endowment is randomly allocated (Spraggon and Oxoby 2009). In contrast, studies by Chan et al (1996Chan et al ( , 1999 and Buckley and Croson (2006) The literature on the impact of the origin of endowment differences on individual behavior in public goods games appears ambiguous.…”
Section: Related Literaturementioning
confidence: 83%
“…Cherry et al (2002) shows that subjects playing a dictator game are less generous with money obtained after a mental task (answering 10 out of 17 GMAT questions correctly) than with a windfall gain. Spraggon & Oxoby (2009) finds the opposite result in a public good game, and Cherry et al (2005) find no effect in a public good game. 3 This literature has shown that social preferences are source dependent.…”
Section: Introductionmentioning
confidence: 86%